Preliminary study of the digestive effects of Chenopodium ambrosioides Linn. (Chenopodiaceae) leaves extracts in goats - Daga, Florian Dadjo (My University, 2013)
The effects of the crude aqueous extract of Chenopodium ambrosioides leaves on food intake and digestibility were evaluated with twelve Sahelian goats weighing about 25 kg. Three experimental groups, each consisting of three animals, were treated respectively with the dose of 1ml, 2ml and 4ml/kg of body weight. Treatment was daily and lasted three days. One control group, receiving the same diet as the experimental groups, was involved. The experiment revealed that the herbal extract induced a highly significant variation (p <0.01) in voluntary feed intake expressed in grams of dry matter (DM) from 366.67 g ± 86 (control group) to 631.67 g ± 106.37 (4ml/kg/BW treated group). Concerning digestibility, the results indicated an increase in the absorption of ash and fibre (39.65 % ± 2.65 to 51.38 % ± 4.91). But the digestibility of protein was only slightly influenced by the herbal extract. Animals treated with 4ml/kg/BW dosage had soft and pasty faeces. The aqueous extract of C. ambrosioides leaves would own interesting digestive effects in small ruminants in the fattening stage or those suffering from indigestion due to rumen stuffing. Further specialized studies may clarify those effects.
Keywords: Sahelian Goats; Food intake; Digestibility Pharmacopoeia; Chenopodiumambrosioides